Cinderella - Lewis, Hara.; Lanza, Barbara (New York : Scholastic, 2004)
In her haste to flee the palace before the fairy godmother's magic loses effect, Cinderella leaves behind a glass slipper, providing a clue for the prince who has fallen in love with her.
"Cartwheel Books."
Keywords: Fairy tales; Folklore